Defamation Through Social Media as a Cyber Crime - Dewanto, Hendro; Wahyudi, Setya (KnE Social Sciences, 2023)
This writing finds a strict interpretation of the criminal act of defamation through social media, where many cases criminalize a person who does not deserve to be called the perpetrator or suspect of defamation. The questions of this writing are how defamation through social media is categorized as a cyber crime and how law enforcement officials should interpret elements of defamation through social media. The results of the study show that, first, defamation through social media is part of a cyber crime. because it is in an electronic and cyberspace environment and secondly, the interpretation of the crime of defamation should be based on the guidelines of the Joint Decree regarding guidelines for the implementation of certain articles in the ITE Law between the Attorney General’s Office of the Republic of Indonesia, the Police of the Republic of Indonesia and the Minister of Communication and Information, Number 229 of 2021 dated June 23, 2021 which is more careful by paying attention to aspects of perpetrators and victims. Suggestions in this writing is outreach to law enforcement officials to comply with this interpretation. Keywords: social media, defamation, cyber crime